Feasible, Efficient and Necessary, without Exception : Working with Sex Workers Interrupts HIV/STI Transmission and Brings Treatment to Many in Need - Steen, Richard; Wheeler, Tisha; Gorgens, Marelize; Mziray, Elizabeth; Dallabetta, Gina (Public Library of Science, 2015)
High rates of partner change in sex work—whether in professional, ‘transactional’ or other context—disproportionately drive transmission of HIV and other sexually transmitted infections. Several countries in Asia have demonstrated that reducing transmission in sex work can reverse established epidemics among sex workers, their clients and the general population. Experience and emerging research from Africa reaffirms unprotected sex work to be a key driver of sexual transmission in different contexts and regardless of stage or classification of HIV epidemic. This validation of the epidemiology behind sexual transmission carries an urgent imperative to realign prevention resources and scale up effective targeted interventions in sex work settings, and, given declining HIV resources, to do so efficiently. Eighteen articles in this issue of PLOS One highlight the importance and feasibility of such interventions under four themes: 1) epidemiology, data needs and modelling of sex work in generalised epidemics; 2) implementation science addressing practical aspects of intervention scale-up; 3) community mobilisation and 4) the treatment cascade for sex workers living with HIV.